Meningkatkan Kerja Sama Siswa Melalui Pembelajaran Kooperatif Tipe Think Pair Share - Ita Rosita; Leonard Leonard (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2013)
Human beings as social creatures need cooperative with others due to their independencies. It means that cooperative is needed by all the people. Recently, some of the problems in education are the students’ cooperative is still not optimal and the low point of students’ achievement in the learning process. In cooperative learning, one of the methods is Think Pair Share method that can improve the students’ achievement. This method is focused on student-center that allows students to think independently forming ideas of their own then they are grouped in pairs to discuss their thoughts and train their social interaction to articulate their ideas and to consider those of others. Improving the students’ teamwork in cooperative learning through Think Pair Share habitually will achieve the purpose of studying.